Single-molecule imaging analysis of Ras activation in living cells - Murakoshi, Hideji (National Academy of Sciences, 2004)
A single-molecule fluorescence resonance energy transfer (FRET) method has been developed to observe the activation of the small G protein Ras at the level of individual molecules. KB cells expressing H- or K-Ras fused with YFP (donor) were microinjected with the fluorescent GTP analogue BodipyTR-GTP (acceptor), and the epidermal growth factor-induced binding of BodipyTR-GTP to YFP-(H or K)-Ras was monitored by single-molecule FRET. On activation, Ras diffusion was greatly suppressed/immobilized, suggesting the formation of large, activated Ras-signaling complexes. These complexes may work as platforms for transducing the Ras signal to effector molecules, further suggesting that Ras signal transduction requires more than simple collisions with effector molecules. GAP334-GFP recruited to the membrane was also stationary, suggesting its binding to the signaling complex. The single-molecules FRET method developed here provides a powerful technique to study the signal-transduction mechanisms of various G proteins.